Total Bakteri Asam Laktat, Total Asam, Dan Sifat Sensoris Minuman Potensi Probiotik Berbasis Kulit Nanas Dengan Variasi Jenis Gula - Della Savira; Yunan Kholifatuddin; Wikanastri Hersoelistyorini; Agus Suyanto (Jurnal Pangan dan Gizi, 2026)
Probiotic drinks are beverage containing good bacteria which are usually made from milk. The probiotic drink in this study used pineapple peel waste as raw material. Pineapple skin contains carbohydrates and reducing sugars which can be used as raw materials for making potential probiotic drinks.The research was conducted to determine the effect of varying types of sugar on total Lactic Acid Bacteria (LAB), total acid, and sensory properties in pineapple peel-based potential probiotic drinks. The pineapple skin juice probiotic drink is fermented using Lactobacillus plantarum for 24 hours. The types of sugar used include stevia sugar, corn sugar, erythritol, cassava sugar and granulated sugar as controls. The method used is a quantitative experimental approach with test parameters for total BAL, total titrated acid, and sensory properties. The results showed that variations in the type of sugar in the pineapple peel-based potential probiotic drink had no significant effect on the amount of LAB, but variations in the type of sugar had a significant effect on the total acid and sensory properties of the pineapple peel-based potential probiotic drink. The best treatment is the stevia sugar treatment.